The figure of Abraham in John 8: text and intertext - Sheridan, Ruth (Library of New Testament studies, 2020)
Intro -- Title Page -- Copyright Page -- Contents -- Acknowledgements -- Abbreviations -- Chapter 1: Introduction -- The range of Abraham's post-biblical 'afterlives' -- Abraham in the Gospel of John: A survey of the secondary literature -- Full-length studies: Horatio Lona and Tineke de Lange -- Shorter studies on Abraham in John 8 -- Shorter studies: Abraham in the narrative and communalworlds of John 8 -- Shorter studies: Abraham and intertextuality -- Focused studies: The 'seed of Abraham' in John 8.31-34 -- Focused studies: The 'works of Abraham' (8.39-47) -- Focused studies: Abraham saw and rejoiced (John 8.56-58) -- Summary and ways forward -- The purpose of this book: Outline and argument -- Chapter 2: Theoretical foundations: Intertextuality -- Introduction -- Reflecting on comparative reasoning in textual analysis -- Intertextuality -- Roland Barthes's theorization of intertextuality -- Textual analysis -- Writerly and readerly texts -- Application to the Gospel of John -- Chapter 3: John 8.31-59: Structure, setting, text -- Introduction -- The problem of the textual addressees: Ch. 8 vv. 30 and 31 -- A tripartite structure for ch. 8 vv. 31-59 -- The unity and thematic coherence of John 7.1-8.59 -- Origins -- Knowledge and belief -- Judgement -- Testimony -- Scripting the Sukkot intertext -- Determining the festival setting of John 7-8 -- Sukkot as cultural code and intertext -- The Torah -- The prophets -- The writings -- Pseudepigrapha -- Philo and Josephus -- Rabbinic literature -- Chapter 4: Seed of Abraham, slavery and sin (John 8.31-36) -- Introduction -- Part 1: Scripting the intertextual field -- The Hebrew Bible -- The Abraham Cycle: Gen. 12.1-9 -- 13.14-16 -- 15.1-20 -- 17.1-27 -- 21.8-14 -- 22.15-19 -- Texts outside the Abraham Cycle: Gen. 26.1-5 -- 26.23-24b -- 28.4-5, 13-15 -- 35.11-12 -- Other texts from the Torah.